EVALUASI IMPLEMENTASI PROGRAM INDONESIA PINTAR DI SMKN 1 LEMBAH MELINTANGKABUPATEN PASAMAN BARAT - Jihan Fakhirah; Agustino Leo (NIAGARA Scientific Journal, 2023)
The Smart Indonesia Program is cash assistance from the government that is given to students whose parents cannot afford to pay for their education (Regulation of the Ministry of Education and Culture of the Republic of Indonesia Number 12 of 2015). The purpose of this study was to evaluate the implementation of the Smart Indonesia Program at SMKN 1 Lembah Melintang, West Pasaman Regency. The problems in this research are the process of distribution and disbursement of aid funds that are not timely, program targets that are not quite right and monitoring and socialization that are still not optimal. The method used in this research is descriptive qualitative research. The researcher uses William N. Dunn's theory with indicators of effectiveness, efficiency, adequacy, alignment, responsiveness and accuracy. The results of the study found that the Evaluation of the Implementation of the Smart Indonesia Program at SMKN 1 Lembah Melintang, West Pasaman Regency, had not been maximized. Due to the lack of supervision or outreach from the education office to the schools regarding the implementation of the program. Suggestions given by researchers include increasing socialization regarding the program to schools, providing knowledge to parents or guardians regarding the use of aid funds, schools to be more careful in recording student assistance recipients so that they are right on target, and increasing active communication between the Education Office and School.